2004
DOI: 10.1021/bi048988n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the β-Carbon Processing Reactions of the Mammalian Cytosolic Fatty Acid Synthase:  Role of the Central Core

Abstract: The properties of the beta-ketoacyl reductase, dehydrase, and enoyl reductase components of the animal fatty acid synthase responsible for the reduction of the beta-ketoacyl moiety formed at each round of chain elongation have been studied by engineering and characterizing mutants defective in each of these three catalytic domains. These "beta-carbon processing" mutants leak the stalled four-carbon intermediates by direct transfer to CoA. However, enoyl reductase mutants leak beta-ketobutyryl, beta-hydroxybuty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…Indeed, the original assignment of Lys-1699 to the ER enzyme was based on the observation that PLP labeling selectively inhibited the ER activity while leaving the other partial reactions unaffected. In addition, Smith and co-workers (34,35) mutated residues in the proposed NADPHbinding sites of the ER (Gly-1672 and Gly-1673) and BKR (Gly-1886 and Gly-1888) enzymes of rat FAS, and they demonstrated that these mutations had selective effects on the two partial activities. Given the extensive data for two NADPH-binding sites, our current hypothesis is that NADPH binding to one cofactor site is sensed by the second cofactor site and, thus, that the result of mutating Lys-1699 has an allosteric effect on the BKR reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the original assignment of Lys-1699 to the ER enzyme was based on the observation that PLP labeling selectively inhibited the ER activity while leaving the other partial reactions unaffected. In addition, Smith and co-workers (34,35) mutated residues in the proposed NADPHbinding sites of the ER (Gly-1672 and Gly-1673) and BKR (Gly-1886 and Gly-1888) enzymes of rat FAS, and they demonstrated that these mutations had selective effects on the two partial activities. Given the extensive data for two NADPH-binding sites, our current hypothesis is that NADPH binding to one cofactor site is sensed by the second cofactor site and, thus, that the result of mutating Lys-1699 has an allosteric effect on the BKR reaction.…”
Section: Discussionmentioning
confidence: 99%
“…16a,33 Each KR 0 protein, as well as redox-active EryKR1 as positive control and NADPH-nonbinding EryKR3 0 as negative control, was prepared at 10 μM in 50 mM sodium phosphate, pH 7.2. Solutions of NADPH (10-μL) of increasing concentration were added to the microplate wells containing 90 μL of purified 10 μM KR protein solution or buffer alone.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…To avoid loss of short fatty acids during evaporation, fatty acids were converted to the potassium salts, solvent was removed by evaporation with nitrogen and the fatty acid salts were derivatized with phenacyl-8 (Pierce). Phenacyl esters were analyzed by reversed-phase HPLC (22). To improve separation of phenacyl esters of short chain fatty acids and lipoic acid, the gradient was modified as follow: 45% solvent B (acetonitrile) for 5 min, then linear gradient to 56% B over 13 min, linear gradient to 90% B over 12 min, and finally linear gradient to 98% B over 9 min.…”
Section: Isolation Purification and Subfractionation Of Bovine Heartmentioning
confidence: 99%